7(2n-3)=5(3n-4)

Simple and best practice solution for 7(2n-3)=5(3n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2n-3)=5(3n-4) equation:


Simplifying
7(2n + -3) = 5(3n + -4)

Reorder the terms:
7(-3 + 2n) = 5(3n + -4)
(-3 * 7 + 2n * 7) = 5(3n + -4)
(-21 + 14n) = 5(3n + -4)

Reorder the terms:
-21 + 14n = 5(-4 + 3n)
-21 + 14n = (-4 * 5 + 3n * 5)
-21 + 14n = (-20 + 15n)

Solving
-21 + 14n = -20 + 15n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-15n' to each side of the equation.
-21 + 14n + -15n = -20 + 15n + -15n

Combine like terms: 14n + -15n = -1n
-21 + -1n = -20 + 15n + -15n

Combine like terms: 15n + -15n = 0
-21 + -1n = -20 + 0
-21 + -1n = -20

Add '21' to each side of the equation.
-21 + 21 + -1n = -20 + 21

Combine like terms: -21 + 21 = 0
0 + -1n = -20 + 21
-1n = -20 + 21

Combine like terms: -20 + 21 = 1
-1n = 1

Divide each side by '-1'.
n = -1

Simplifying
n = -1

See similar equations:

| -17=4x-6 | | 10x+9=6x+25 | | 10x-22=68 | | x^2+x+2+x+2=100 | | x(x-5)=36 | | 4x^2-6x+2=0 | | 3(n+2)+4n=4(n+2)+4 | | 41+2(3x+6)=95 | | 2(3)-2(4x)+7=0 | | (2*a)+17= | | 3(n+2)-2=4(n-4)-4(n-11) | | 118-(3*b)= | | x(x-8)=-15 | | -3x^2+36x-72=0 | | 25x^2=100 | | 8(2x-1)=72 | | X+46=72 | | 5d-3.3=7.5 | | 17x-8x-9=76-40 | | n=15+2m-4 | | 5(3c-c)+3=43 | | (3x+2)(x+1)=4 | | 2w+9w+2w+8w+7w+w= | | 4a-2=7a-6 | | 6f+30=2f-8 | | 4(x+7.50)=40 | | 118-(3xb)= | | 4x-8=x+25 | | 49-2x=7x+16 | | 11-10x=103-38x | | 139-3x=6x+22 | | 2x+3(x-1)=27 |

Equations solver categories